SPET Monitoring of Perfusion Changes in Auditory Cortex following Mono- and Multi-Frequency Stimuli - Rossi, Giuseppe de; Paludetti, Gaetano; Nardo, Walter di; Calcagni, Maria L.; Giuda, Daniela di; Almadori, Giovanni; Galli, Jacopo (Nuklearmedizin - NuclearMedicine, 1996)
Aim: In order to assess the relationship between auditory cortex perfusion and the frequency of acoustic stimuli, twenty normally-hearing subjects underwent cerebral SPET. Methods: In 10 patients a multi-frequency stimulus (250-4000 Hz at 40 dB SL) was delivered, while 10 subjects were stimulated with a 500 Hz pure tone at 40 dB SL. The prestimulation SPET was subtracted from poststimulation study and auditory cortex activation was expressed as percent increments. Results: Contralateral cortex was the most active area with multi-frequency and monofrequency stimuli as well. A clear demonstration of a tonotopic distribution of acoustic stimuli in the auditory cortex was achieved. In addition, the accessory role played by homolateral acoustic areas was confirmed. Conclusion: The results of the present research support the hypothesis that brain SPET may be useful to obtain semiquantitative reliable information on low frequency auditory level in profoundly deaf patients. This may be achieved comparing the extension of the cortical areas activated by high-intensity multifrequency stimuli.
Keywords: Brain SPET; auditory cortex perfusion; mono- and multi-frequency acoustic stimuli